Geography and the integration movement in the Anglophone Caribbean - Griffin, Clifford E. (2000)
Seeks to provide a fuller understanding and explanation of the integrative and disintegrative tendencies in the Anglophone Caribbean. Explains theoretically the basis for the existence of self-determination agendas. Shows how geography, exploitation, neglect and historical memory contribute to the emergence of self-determination movements. Argues from a policy perspective that these self-determination agendas must become integral parts of the policy discourse if a region is to achieve its proposed level of integration.